Finite element analysis of severe plastic deformation of difficult-to-work material by equal-channel angular pressing at ambient temperature - Jamian, Saifulnizan; Sato, Hisashi; Fujiwara, Eri Miura; Watanabe, Yoshimi (Japan Society of Applied Physics, 2011)
An alternative technique of the equal-channel angular pressing (ECAP) process for difficult-to-work materials at ambient temperature is proposed by embedding a difficult-to-work material into an easy-to-work material. The easy-to-work material as a host material assists the deformation of the difficult-to-work material. The ECAP process is simulated by the finite element method (FEM). For this study, Ti as the difficult-to-work material is embedded into an Al-based functionally graded material (FGM) matrix. FEM is conducted with Ti embedded into a different host material type as well as a different die channel geometry. The strain distribution of the specimen after a single ECAP pass is analyzed. From the obtained results, it is found that the strain distribution in Ti is strongly influenced by the host material and the shape of the die channel